Learning from co-housing initiatives: Between Passivhaus engineers and active inhabitants - Tummers, Lidewij Chantal (A+BE | Architecture and the Built Environment, 2017)
Following the UN world summits on Climate Change (Paris 2015) and Habitat (Quito 2016), most European cities assume an active role to implement internationally agreed goals related to climate change, translated in the so-called New Urban Agenda. At the same time, the urban housing market is increasingly inaccessible for low- and middle-income households. To overcome problems such as failing housing supply and high energy-bills, groups of residents take initiatives to create and manage housing projects collectively; these initiatives are further indicated as ‘co-housing’. The aim of this study is to create deeper understanding of the current rise of co-housing in Europe, and what it could mean in urban policies addressing energy transition and climate change. There are two domains where co-housing can become an important asset for urban development: design and maintenance of (semi-)public space for climate change mitigation, and the transition to a circular metabolism in housing. Based on empirical data, this thesis concludes that co-housing projects present relevant models and approaches for reducing the energy consumption and for integrating renewable energies in the general housing stock. Engineers can learn from co-housing pioneers to advance the targets for energy-transition and further develop sustainable cities. The thesis contributes to the emerging body of knowledge with a new understanding of co-housing, analysing its ‘key-features’ with an interdisciplinary framework, in a European context. It adds a new perspective to existing co-housing research, which is dominated by social sciences, by drawing attention to the physical characteristics of co-housing, produced in architectural, planning and engineering processes (the technosphere). The choices made during design and building are not only shaped by the residents’ aims and perception of sustainability, but also influenced by technosphere-related institutions, such as the building-components industry, energy or waste networks and providers, and planning regulations. The professional partners for the projects, such as housing associations and engineers, are equally affected by the institutional context, but their position is different from that of residents. They may for example be more anchored in governmental or professional regulations. To structure this dynamic, the research distinguishes three interrelated aspects: ACTORS / involved in the (realisation of) projects: social practices of residents and their professional partners in co-creation. CONTEXT / the structural forces surrounding the projects, specifically the macroinstitutional regimes. This also includes culturally determined interpretations of sustainability, technology, participation, societal roles, sharing, and so on. TECHNOSPHERE / specifically building technology and utilities, focussing on energyrelated design and engineering of the co-housing projects. The thesis is primarily based on qualitative methods, as it found that reliable quantitative data are as yet unavailable. Looking for effective low-impact energysolution in co-housing, quantitative data remain however necessary and this thesis elaborates on pitfalls and possibilities for their accumulation. Empirical material from Dutch case-studies form the core of the research. Examples were also taken from countries where the re-emergence of co-housing is most visible and articulate: Belgium, France, Germany, the UK and Switzerland. Co-housing continues to develop and gain experiences with competences, such as communication skills and the ability to work cross-disciplinarily. The building industry and engineering professions increasingly call for such capabilities, but resident-led urban development have not yet entered the urbanism and engineering curricula. Therefore, opportunities should be provided for future professionals not only to acquire such capabilities but also to address fundamental questions related to residentinvolvement and democracy. This will enable future professionals to create a balance between ‘bottom-up’ articulated needs on the quality of living environments with large-scale investments in new urban energy, mobility and mutual care networks.